The Impact of Money Politic in the Local Elections in Indonesia - Abdiellah, Muhammad Asyraff; Muharram, Dany Rahmat; Julianingsi, Julianingsi (Journal of Contemporary Local Politics, 2022)
Indonesia is a state of law. In essence, everyone must follow the existing rules. It started off well small to large. Likewise, what is meant by the Indonesian state is a democratic country where the center of power is in the hands of the people. Elections are a form of progress to prioritize the community and create leaders with a high sense of unity and justice. Overall, elections are a sign of supreme power in the hands of the people. Through elections, the assertion of national power can be achieved with some of the powers and rights of the public over representatives of the government and parliament. But in fact, violations often occur both in the Pilkada process and in parliamentary elections. These violations included fraudulent campaign activities in the form of donations of money and goods to tempt the public to vote for a candidate during the election. In a democracy, the development of money politics slowly undermines the principle, because the people's voice can be redeemed with money.